Diversifikasi Produk UMKM PASS Nanas Berbasis Limbah Nanas Melalui Penerapan Teknologi Tepat Guna - Tsamroh, Dewi 'Izzatus; Sasongko, Muhammad Ilman Nur; Santi, Fitriana; Herawati, Andini Sofia; Azhar, Moh. Na'im (Universitas Harapan Bangsa, 2025)
Pass Nanas MSME is a pineapple processing business unit in Kediri Regency that produces pineapple juice beverages. However, it faces challenges in managing production waste, particularly pineapple peels, which have only been used as animal feed. This issue affects business sustainability but also presents an opportunity to create added value through product innovation. This community service program aimed to support product diversification by utilizing pineapple peel waste into nata de pina with the help of a heavy duty blender. The program was carried out through field observation, needs analysis, training in nata de pina production, technical assistance in machine operation, and evaluation. The results showed that pineapple peel can be processed into nata de pina of good quality, with potential to be marketed as a functional food product. This innovation not only reduces organic waste but also expands product variety, thereby improving the competitiveness of the MSME in local and regional markets. Moreover, the program enhanced the partner’s skills in waste utilization, introduced the concept of a circular economy, and strengthened the business sustainability of Pass Nanas MSME.